KINERJA PELAYANAN INFRASTRUKTUR JALAN NASIONAL DI KAWASAN WISATA - Nugroho, Anjang; Nicholas, Nicholas (Civil Infrastructure Engineering and Architectural Design, 2018)
Development of tourism areas was planned to support the target of 20 million foreign tourists and 275 million domestic tourists visiting Indonesia in 2019. In order to accommodate these tourists, road infrastructures need to be improved so that its quality and quantity meets the characteristics of tourism area. Importance and satisfaction analysis of road service performance was used as an approach to determine the public road criteria which were needed to be improved. Results showed that the trips security to the tourism area, the placement of signage and the trip convenience were the criteria that have very high importance and satisfaction rating and needs to be continued maintained. However the criteria which were needed to be improved were the number of road lighting and the number of roadside station/rest area.